Human capital and sustainable development in Nigeria: How can economic growth suffice environmental degradation? - Moses Clinton Ekperiware; Timothy O. Olatayo; Abiodun Adeyemi Egbetokun (Kiel Institute for the World Economy (IfW), 2017)
The motivation for sustainable development is universal but strides to achieve it have been mixed in the literature with some schools of thought's position that economic growth is anti-sustainable development. The crux of this study is to examine the coordinating role (as engine) of human capital among the three pillars of sustainable development in Nigeria from 1981 to 2014 with data from the World Development Indicators (WDI) 2014. Descriptive statistics is used to illustrate observed trend in human capital and the pillars of sustainable development (economic development, social development, and environment protection). Vector Auto-Regression (VAR) econometric technique was used to measure trade-offs, effects, interrelationships, and scenario analysis of these indicators and the prominent role of increased human capital scenario in achieving sustainable development. The analyses of the interrelationship and scenario effects of increased human capital formation showed that environmental degradation negatively affected human capital formation but increases with economic growth. A scenario of further increase in human capital development reduces environmental degradation and increases economic growth in Nigeria. Hence, human capital formation leads to sustained economic growth with reducing environmental degradation.
Keywords: O1; Q01; 330; sustainable development; human capital development; population; and environmental degradation; economic development